Corrosion studies of Alx-Ni insitu intermetallics reinforced Al metal matrix composites. (2020) - Abuthakir, J.; Subramanian, R.; Kavitha, M.; Venkatesh, G.; Krishna kumar, K.; Manikandan, P.
Abstract: Insitu intermetallics reinforced Al Metal Matrix Composites (MMCs) have been receiving wide interests in the recent research studies due to their improved mechanical and metallurgical properties compared to conventional ceramic reinforcements. Literature review indicates that preparation route for intermetallics based Al MMCs are mainly Friction stir processing (FSP), powder metallurgy and pressure infiltration routes. FSP route is limited to surface composites whereas other routes have limitations in achieving the required strength. In the present Ni based insitu intermetallics have been reinforced in the Al alloy by stir casting route. Synthesized composite samples were solutionized and age hardened. Hardness test has been performed for the prepared samples in the as-cast and age hardened condition. Selected samples were characterized successfully using optical microscopy and scanning electron microscopy with Energy dispersive spectroscopy (EDS) attachment. Results reveal that Ni based intermetallics have been successfully formed in the matrix with good interfacial bonding. Microstructural analysis reveals that nickel addition resulted in grain refinement due to the formation of Ni based insitu intermetallics. EDS results reveal that Ni based intermetallics have been formed and Spot analysis indicates excellent interfacial between the matrix and the intermetallic compounds in the heat–treated condition. Corrosion studies reveal that corrosion rate decreases with increase in nickel addition in the heat treated condition due to the formation of intermetallic compounds.